Progress of Research on Chinese Medicine Intervention in Ferroptosis for Osteoarthritis - Li, Mengyuan; Wang, Li (Journal of Contemporary Medical Practice, 2025)
Osteoarthritis is a common chronic joint disease that brings great pain and life burden to patients. In recent years, ferroptosis, a novel mode of programmed cell death, has gradually gained attention in the pathogenesis of osteoarthritis. As a traditional treatment method, Chinese medicine has the advantages of multi-targeting and overall regulation in regulating ferroptosis in osteoarthritis. This review discusses the mechanisms of TCM in regulating ferroptosis-related signaling pathways, anti-oxidative stress, inhibition of inflammatory responses, and the key regulators and regulatory pathways of ferroptosis in osteoarthritis, and comprehends the current status of the research on the targeting of active ingredients of TCM to inhibit ferroptosis, so as to provide reference for the research on the mechanism of TCM in treating osteoarthritis and for the research and development of drugs.